The Influence of Agricultural Practices, the Environment, and Cultivar Differences on Soybean Seed Protein, Oil, Sugars, and Amino Acids - Nacer Bellaloui; Angela M. McClure; Alemu Mengistu; Hamed K. Abbas (Plants, 2020)
Information on the effects of agricultural practices such as seeding rate (S), row spacing (RS), herbicide apical treatment (T), and nitrogen application (N) on soybean seed nutrition (protein, oil, fatty acids, sugars, and amino acids) is limited. Although seed composition (nutrition) constituents are genetically controlled, agricultural practices and environmental conditions significantly influence the amount and quality of seed nutrition. Therefore, the objective of this research was to understand the responses of these seed composition constituents to these practices, the environment, and cultivar differences. Two-field experiments were conducted, in 2015 and 2016, in Milan, TN, USA. The experiments were irrigated with four replications and included: two soybean cultivars, two seeding rates, three different row spacings, two N rates, and Cobra herbicide apical treatment. The results showed significant effects of S, RS, N, and T on some seed composition constituents, including protein; oleic, linolenic, and stearic acids; sugars; and some amino acids. The current research demonstrated that single or twin row with a seeding rate of 40,000 seeds ha−1 resulted in higher protein, oleic, some sugars, and some amino acids. However, a high seeding rate of 56,000 seeds ha−1 resulted in lower protein, oleic acid, some sugars, and some amino acids due to plant competition for soil nutrients. Herbicide apical application of Cobra1X resulted in higher linolenic acid and some amino acids. Application of nitrogen resulted in higher protein, linolenic, and some amino acids. This research is beneficial to the scientific communities, including breeders and physiologists through advancing knowledge on the interactions between cultivars and environment for seed nutritional quality selection, and to soybean producers through consideration of best agricultural management to maintain high seed nutritional qualities.